3D cable-based parallel robot simulation using PD control - Inel, F.; M. M., Noor (IOP Publishing, 2020)
In this paper, we present a simulator that has been developed using PD control to study 3D cable-based parallel robot with four cables. The proposed control technique is widely used for dealing with linear systems uncertainties, in this context; we investigated to use the Runge Kutta method of 4th order for solving non-linear partial differential equations of our system. The main contribution of this work is firstly: modelling of differential equations of our system. Secondly, the PD control applied to the dynamic model for different trajectories in order to test the accurate tracking of the robot to a desired trajectory. The effectiveness of the proposed control strategy is improving the robot performance in terms of tracking a desired path.